Nursing Strategies to Avoid DVT among Postoperative patients: Comprehensive review - Rehab Duhaim Alanezi, Ather Modhi Jadaan Alenazi, Shuaa Ayidh Lafi Alenzi, Ashwaq Mayouf Alruwaili, Aljawhara Manawar Alanez,; Mariam Saad Alrashed , Latifa Osaifer Alenazi, Rehab Awadh Sluaman Alanzi, Eidah Saud Bushry Alanezi, Sitah Alsahali Hezam Alanazi, (Journal of International Crisis and Risk Communication Research, 2024)
Nurses play a crucial role in the management of deep vein thrombosis (DVT) in the emergency department (ED), serving as the first line of assessment and intervention. Their responsibilities include conducting thorough patient assessments, utilizing clinical judgment to identify risk factors for DVT, and recognizing symptoms such as swelling, pain, and tenderness in the affected limb. Education is also a key component of their role; nurses provide patients with information about DVT, its potential complications, and the importance of early intervention. Additionally, they collaborate with physicians to facilitate timely diagnostic imaging and the initiation of appropriate treatment protocols, including anticoagulation therapy. Beyond immediate clinical management, nurses are integral in developing and implementing preventive strategies for at-risk patients. This includes mobilization of patients post-surgery or during long hospital stays and the application of compression devices. Nurses also monitor for any adverse reactions to treatments and are responsible for patient education on lifestyle modifications and the importance of follow-up care. By fostering a supportive environment and maintaining open communication, nurses help to ensure that patients understand their condition and follow the prescribed management plans, ultimately improving outcomes in the ED setting.